Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2014
DOI: 10.1145/2556288.2557099
|View full text |Cite
|
Sign up to set email alerts
|

Persuasive technology for overcoming food cravings and improving snack choices

Abstract: A central challenge in weight management is the difficulty of overcoming desires for excessive and unhealthy food. Yet, studies show that when people are able to resist their desires for unhealthy choices, they experience pride and satisfaction. In order to alleviate the former and support the latter, we designed, implemented and tested a mobile application for improving snacking behavior. Our application delivers a food craving reduction intervention at the moment of need and allows users to track how often t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…Knäuper et al (2011) also measured consumption of the specific item craved and found no effect of task on indulgence. In contrast, Kemps and Tiggemann (2013) and Hsu et al (2014) found that visual interventions decreased overall consumption. This may be an important difference that future research could address by measuring both overall consumption, for any foods, and consumption of the specific foods for which craving is reported.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Knäuper et al (2011) also measured consumption of the specific item craved and found no effect of task on indulgence. In contrast, Kemps and Tiggemann (2013) and Hsu et al (2014) found that visual interventions decreased overall consumption. This may be an important difference that future research could address by measuring both overall consumption, for any foods, and consumption of the specific foods for which craving is reported.…”
Section: Discussionmentioning
confidence: 85%
“…Third, this study recruited an unrestricted sample whereas Kemps and Tiggemann (2013), Hsu et al (2014) and Knäuper et al (2011) recruited participants who had a high number of food cravings, wanted to reduce their snacking behaviour, or wanted to reduce their cravings. Those populations may have had stronger motivation to decrease their indulgence rates whereas our sample may have been contented with their indulgence rates and still have chosen to indulge even when their craving was weakened.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were no such changes for groups who formed implementation intentions to reduce their craving, without explicit imagery instructions, or who performed the verbal task of counting backwards. Hsu et al (2014) trialed a smartphone app (iCrave), which gave written instructions to create specified neutral images when users craved snacks, and asked users to record both snacking and successful behavioral control. Over a week, community volunteers using iCrave ate fewer unhealthy snacks (but similar amounts of healthy snacks) as others who simply tracked their snacking.…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…Food decision making is influenced by factors that vary across and within individuals, depending on timing and context, cultural, social and personal differences as well as an own personal system that balances all previous factors [9]. Previous work in HCI explored persuasive technologies that support an individual's decision process of, for example, overcoming unhealthy cravings [6]. Svensson et al [11] showed an affirmative influence others have on user's recipe choice when being navigated through a recipe recommender system by the means of other user's actions.…”
Section: Background and Related Workmentioning
confidence: 99%